Ecology of malaria infections in western lowland gorillas inhabiting Dzanga Sangha Protected Areas, Central African Republic - Mapua, Mwanahamisi I; Qablan, Moneeb A; Pomajbíková, Kateřina; Petrželková, Klára J; Hůzová, Zuzana; Rádrová, Jana; Votýpka, Jan; Todd, Angelique; Jirků, Milan; Leendertz, Fabian H; Lukeš, Julius; Neel, Cecile; et al. (Parasitology, 2015)
African great apes are susceptible to infections with several species of Plasmodium, including the predecessor of Plasmodium falciparum. Little is known about the ecology of these pathogens in gorillas. A total of 131 gorilla fecal samples were collected from Dzanga-Sangha Protected Areas to study the diversity and prevalence of Plasmodium species. The effects of sex and age as factors influencing levels of infection with Plasmodium in habituated gorilla groups were assessed. Ninety-five human blood samples from the same locality were also analysed to test for cross-transmission between humans and gorillas. According to a cytB PCR assay 32% of gorilla's fecal samples and 43·1% human individuals were infected with Plasmodium spp. All Laverania species, Plasmodium vivax, and for the first time Plasmodium ovale were identified from gorilla samples. Plasmodium praefalciparum was present only from habituated individuals and P. falciparum was detected from human samples. Although few P. vivax and P. ovale sequences were obtained from gorillas, the evidence for cross-species transmission between humans and gorillas requires more in depth analysis. No association was found between malaria infection and sex, however, younger individuals aged ≤6 years were more susceptible. Switching between two different Plasmodium spp. was observed in three individuals. Prolonged monitoring of Plasmodium infection during various seasons and recording behavioural data is necessary to draw a precise picture about the infection dynamics.
Keywords: Feces; ekosystém; cytochromy b; Conservation of Natural Resources; polymerázová řetězová reakce; Central African Republic; Cytochromes b; Polymerase Chain Reaction; African great apes; malárie vivax; mužské pohlaví; nemoci lidoopů; lowland gorilla; Plasmodium spp; malárie; Ape Diseases; zachování přírodních zdrojů; ženské pohlaví; Malaria, Falciparum; zvířata; feces; Humans; malaria; Plasmodium ovale; fylogeneze; Středoafrická republika; tropická malárie; Plasmodium falciparum; Gorilla gorilla; Malaria, Vivax; Plasmodium vivax; Female; Ecosystem; Phylogeny; Malaria; lidé; Male; Animals